2020
DOI: 10.1177/0098628320977265
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Movement-Integrated Learning Activities in Statistics and Research Methods Courses

Abstract: Background: College students majoring in psychology often report low interest and engagement in statistics and research methods courses. Objective: The purpose of the current study was to examine potential benefits of integrating movement with learning activities in Introduction to Statistics and Research Methods courses at the college level. Method: A quasi-experimental design examined movement-based learning activities compared to traditional learning activities during class periods. Students’ perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Teaching today is made even more difficult by the fact that modern students are often looking at their phones during class time. Some research suggests that students are less interested in textbook and whiteboard and instead are move motivated by content they can interact with like games 8,9,10,11 . Studies suggest that without active learning strategies, within 10-15 minutes of a lecture starting, there will be a decline in student attention 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Teaching today is made even more difficult by the fact that modern students are often looking at their phones during class time. Some research suggests that students are less interested in textbook and whiteboard and instead are move motivated by content they can interact with like games 8,9,10,11 . Studies suggest that without active learning strategies, within 10-15 minutes of a lecture starting, there will be a decline in student attention 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Teaching today is made even more difficult by the fact that modern students are often looking at their phones during class time. Some research suggests that students are less interested in textbook and whiteboard and instead are more motivated by content they can interact with, and games 7,9,10,12 . One mobile application I see students playing before, after, and unfortunately even during class is Pokémon Go.…”
Section: Introductionmentioning
confidence: 99%
“…5 Use of exergames, games that promote exercise, have been linked to positive health benefits as well as educational benefits 6,9 . Studies have linked physical exercise to positive cognitive and academic performance outcomes and suggested that all ages can benefit from physical activity in the classroom 9,12 .…”
Section: Introductionmentioning
confidence: 99%